High refractive index and low-birefringence polyamides containing thiazole and naphthalene units - Javadi, Ali (Royal Society of Chemistry, 2015)
Highly refractive and solution processable polyamides (PAs) were synthesized by the introduction of thiazole rings, naphthalene groups, and thioether linkages. These PAs were synthesized by the polycondensation of a new diamine monomer, 5,5'-thiobis(2-amino-4-(2-naphthyl)thiazole) (DA), with various aromatic diacids. The bulky pendant naphthyl units endowed the resulting PAs with non-coplanar structures and excellent solubilities in organic solvents. The obtained PAs showed high thermal stability, with 10% weight loss temperatures exceeding 478°C under nitrogen and 431°C in air atmosphere, while their glass transition temperatures were in the range of 194-229°C. The synergic effects of the thiazole groups, naphthyl substituents, and thioether linkages provided PAs with very high refractive indices of up to 1.7701 at 632.8 nm, along with small birefringences (<0.0076) and high Abbe's numbers. The structure-property relationships of these PAs due to the presence of naphthyl substituents were also studied in detail by comparing the results with the previously reported analogous PAs